Pour la protection des assurés en cas de faillite de l’assureur - Robitaille, Jean (Assurances)

(untitled) (HEC Montréal, 1986)
Following is a summary by Mr. Jean Robitaille on the guarantee fund proposal which the Insurance Bureau of Canada presented to the Federal Government. Here are some of the highlights: following an insurer's bankruptcy, the fund will pay to the insured the balance of a claim's settlement provided certain specific conditions are met. Providing up to $200,000 per insured, this fund is designed to prevent the insurer from incurring any loss once the insurer's assets have been liquidated. It seems likely that some provincial governments will soon adopt this proposal which is fully supported by the Federal Superintendent of Insurance and the Ministry of Finance.